Cardiac Rupture from Blunt Chest Trauma Diagnosed on Transesophageal Echocardiography. (February 2015) - Gerlach, Rebecca; Mark, David; Poologaindran, Anujan; Tanzola, Rob
Abstract : Supplemental Digital Content is available in the text.